Marketing Tourism, Hospitality and Leisure in Europe - Horner Susan; Swarbrooke John (International Thomson Business Press, 1996)
A European perspective on all the key areas of Marketing. Preface, Acknowledgements, Introduction, The European Dimension, The Marketing Mix and Tourism and Leisure and Hospitality, Marketing Planning in Tourism and Leisure and Hospitality, Marketing in Different Sectors of Tourism and Leisure and Hospitality, Topical Issues in Tourism and Leisure and Hospitality Marketing in Europe, The Wider Context, Case Studies, Index.